DIFFERENT TEACHING STRATEGIES AND METHODS APPLIED AT PHE CLASSES –EXPERIENCES OF CLASSROM TEACHERS - Orce Mitevski; Biljana Popeska; Katerina Mitevska Petrusheva; Snezana Jovanova Mitkovska (Faculty of Physical Education Sport and Health - Skopje, 2020)
Effectiveness of physical education teaching process and quality of physical education classes depends on many factors. Well-selected and correctly applied teaching strategies and methods could have positive impact of the quality and effectiveness of Physical and health education (PHE) teaching process. The purpose of the study is to determine different teaching strategies and methods that teachers used physical education classes. Study sample was comprised from 134 generalist classroom teachers from 15 primary schools in Macedonia. Teachers were included in the study that examined their attitudes regarded use of different strategies and methods that they applied in different phases at PHE classes. According the obtained results, nearly all teachers (93%) use movement games on regular bases in first and last phase of PHE classes, 83% use them in main part. Traditional movement games are often implemented in PHE classes (44%). Music and technology are mainly used in main part of PHE classes by 43% of teachers, while more than half of interviewed teachers use classroom based active breaks with movements at another subject. In summary, we would underline that movement games, music, traditional games, technology, different tools that integrate PHE and other subject contents are some of the strategies that teachers use at PHE classes. Such strategies implemented at PHE teaching process could benefit with greater effectiveness, interest and active participation of children.
Keywords: effectiveness, approaches, physical education, teachers